The Role of Apolipoproteins in Dengue Infection: A Review - Ahmad, Radzi Ikhsan; Nor, Fadzilah Mohd; Mui, Wang Seok; Abdul Rahman, Thuhairah Hasrah (IIUM Medical Journal Malaysia, 2021)
The re-emergence of the dengue virus in recent decades has significantly increased with almost 40%-50% of the world’s population being at risk. Meanwhile, cholesterol and its components, apolipoproteins, were found to play a vital role in dengue infectivity and the development of severe dengue. This review attempts to address the functional importance of cholesterol and related apolipoproteins in dengue virus pathogenesis and to identify the potential utilisation of this relationship in future diagnosis and management of dengue. The literature search was conducted using a computer-based electronic search on dengue infection with cholesterol and human lipoproteins from September 2017 to June 2019 through three main search engines: MEDLINE (OVID), PubMed, and Science Direct using the keywords including Flaviviruses, characteristics of dengue virus, the pathogenesis of dengue, enhancement of dengue, metabolism of cholesterol, cholesterol pathway and human lipoproteins in association with dengue. Dengue virus manipulates lipid raft integrity and utilizes cholesterol components and apolipoproteins for virus internalisation through LDLr and SR-BI receptors. Infectivity of the dengue virus correlated with a decrease in the cholesterol content of the virions. High cholesterol levels in the endoplasmic reticulum promote replication complexes formation of dengue virus. Cholesterol is needed for NS1 secretion which is essential in viral replication, dengue pathogenesis, and host immune evasion. Levels of cholesterol and its related components contributed to the development of severe dengue. The interplay between cholesterol and cellular proteins lead to significant effect in all aspects of the dengue virus replication cycle from viral entry to release.